Antioxidant homoisoflavonoids from Polygonatum odoratum. (1st November 2015) - Zhou, Xiaoling; Yuping, Zhang; Zhao, Huading; Liang, Junsheng; Zhang, Yi; Shi, Shuyun
Graphical abstract: Highlights: Eleven antioxidant homoisoflavanones including three new compounds were identified. Stepwise HSCCC with Sephadex LH-20 was used to isolate antioxidants. Antioxidant activity of isolated compounds was evaluated. Abstract: Polygonatum odoratum is widely used as a traditional food supplement and herbal medicine with strong antioxidant activity. However, systematic investigation of its antioxidants was limited. Ethanol extract of P. odoratum was fractioned on macroporous absorptive resin (D101) column. A bioassay-guided purification of flavonoid-rich fraction (IC50 value at 74.1 ± 11.9 μg/mL for DPPH scavenging) was realised via high-speed counter-current chromatography (HSCCC) using petroleum ether–ethyl acetate–methanol–water (2:3:3:2, v/v/v/v) as the solvent system combination with Sephadex LH-20 column chromatography (CC) eluting with MeCN–MeOH (1:1, v/v). Three novel homoisoflavonoids (1 –3 ), along with eight homoisoflavonoids (4 –11 ), were isolated. Their structures were elucidated by interpretating various spectroscopic data. All the isolated homoisoflavonoids showed potent antioxidant activities, while compounds1, 4, and6 with dihydroxylated B-rings exhibited stronger antioxidant activities (IC50 values at 3.8 ± 0.5, 4.9 ± 0.3 and 3.9 ± 0.4 μg/mL) than ascorbic acid (IC50 value at 5.3 ± 0.6 μg/mL).